Multi mean garch approach to evaluating hedging performance in the crude palm oil futures market - Zainudin, Rozaimah; Shaharudin, Roselee Shah (Penerbit Universiti Sains Malaysia, 2011)
This paper provides evidence of hedging performance in the crude palm oil market using risk minimisation and the investor's utility function measurement. We use the spot and futures crude palm oil daily prices from the period of January 1996 to August 2008. Using a dynamic model, we estimate three different mean specifications that involve the intercept, Vector Autoregressive (VAR) and Vector Error Correction Model (VECM) within the Baba, Engle, Kraft and Kroner (BEKK) model. The risk minimisation results exhibit that the Intercept-BEKK and VAR-BEKK models tend to give the most variance reduction within the in-sample and out-sample analysis, respectively. However, Intercept-BEKK remains to outcast the other models in giving the most utility function. The empirical evidence shows that different mean specifications will generate varying hedging performance results, especially in relation to the risk minimisation result. However, the difference in the performance among the tested models is small, especially within the investor's utility function measurement. Since a more sophisticated model does not warrant better hedging performance results, we suggest that a parsimony model may be appropriate when improvising the hedging performance. © Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2011.